Locoregional Flap Reconstruction Following Oromaxillofacial Oncologic Surgery in Dogs and Cats: A Review and Decisional Algorithm - Guzu, Michel; Rossetti, Diego; Hennet, Philippe R. (Frontiers in Veterinary Science, 2021)
Primary treatment of most oromaxillofacial tumours in dogs and cats is resective surgery. Management of malignant tumours may be very challenging as wide/radical free-margin surgical removal must be achieved while preserving vital functions. Removal of orofacial tumours may result in large defects exposing the oral cavity or creating a communication with the nasal, pharyngeal or orbital cavities. Such defects require orofacial reconstruction in order to restore respiratory and manducatory functions. The veterinary surgeon must be familiar with reconstructive techniques in order to prevent the inability of closing the defect, which could lead to an insufficient resection. Small oral defects exposing the nasal cavity are best closed with local random mucosal flaps. Closure of large oral defects may be better achieved with a facial or major palatine-based axial-pattern flap. Small to moderate facial defects can be closed with local advancement or transposition skin flaps. Reconstruction of large facial defects often requires the use of locoregional axial pattern flaps such as the caudal auricular, the superficial temporal or the facial (angularis oris) myocutanous axial pattern flaps. Recent publications have shown that the facial (angularis oris) flap is a very versatile and reliable flap in orofacial reconstructive surgery. A surgical decision algorithm based on the size, nature and location of the defect is proposed.